2021
DOI: 10.1097/md.0000000000026510
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic acid nephropathy

Abstract: we inadvertently used an incorrect image. We thought we were showing Aristolochia clematitis as this was how the plant was described by Science Photo Library, which supplied the image. Science Photo Library has since confirmed to us that its supplied image was not of Aristolochia clematitis. The real Aristolochia clematitis is shown below.⇓

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recent research has highlighted apoptotic and inflammatory mechanisms associated with AA-induced nephropathy. 33 Studies conducted in both human and rodent animal models have demonstrated that AAN is characterized by inflammation and damage to the renal tubules and interstitial tissue in the kidneys. 15,34,35 Our research, along with other prior investigations in zebrafish, has demonstrated that exposing zebrafish embryos to AA results in a significant increase in the expression of proinflammatory genes, including mpo and tnfα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has highlighted apoptotic and inflammatory mechanisms associated with AA-induced nephropathy. 33 Studies conducted in both human and rodent animal models have demonstrated that AAN is characterized by inflammation and damage to the renal tubules and interstitial tissue in the kidneys. 15,34,35 Our research, along with other prior investigations in zebrafish, has demonstrated that exposing zebrafish embryos to AA results in a significant increase in the expression of proinflammatory genes, including mpo and tnfα.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has highlighted apoptotic and inflammatory mechanisms associated with AA‐induced nephropathy 33 . Studies conducted in both human and rodent animal models have demonstrated that AAN is characterized by inflammation and damage to the renal tubules and interstitial tissue in the kidneys 15,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…As early as in the 1960s, Chinese scholars had presented cases of acute renal failure caused by excessive doses of the Chinese herbal medicine Mutong [ 7 ]. In 1993, Belgian researchers first presented cases of chronic progressive kidney failure caused by consumption of weight loss pills containing aristolochic acid [ 8 ]. In the twenty-first century, aconitine poisoning was also frequently reported [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the Aristolochia species have been excluded from the Chinese pharmacopeia and banned to utilize for medicinal purposes in many countries (Kim and Lim, 2019). Yet the conflict between the medicinal value and potential nephrotoxicity and teratogenicity makes the illegal addition of Aristolochia in medicines and health products still rampant (Maggini et al, 2018;Ji et al, 2021). Recently, modern studies gradually discovered the new bioactivities of Aristolochia species such as insecticidal, anti-bacterial, antinociceptive, and anti-inflammatory effects (Kuo et al, 2011;Salome et al, 2020).…”
Section: Introductionmentioning
confidence: 99%